Prevalence of CCR5delta32 in Northeastern Iran - Amir Tajbakhsh; Mostafa Fazeli; Mehdi Rezaee; Faezeh Ghasemi; Mastoureh Momen Heravi; Aida Gholoobi; Zahra Meshkat (BMC, 2019)
Abstract Background A 32-base pair deletion (∆32) in the open reading frame (ORF) of C-C motif chemokine receptor 5 (CCR5) seems to be a protective variant against immune system diseases, especially human immunodeficiency virus type 1 (HIV-1). We aimed to assess the frequency of CCR5∆32 in the healthy Iranian population. Methods In this study, 400 normal samples from Khorasan, northeastern Iran, were randomly selected. The frequency of CCR5∆32 carriers was investigated using PCR analysis. Allele prevalence and the fit to the Hardy-Weinberg equilibrium were analyzed. Results The prevalence of CCR5∆32 in the northeastern population of Iran was 0.016. Four hundred samples were studied, among which one with CCR5 ∆32/∆32 and 11 with CCR5 Wild/∆32 genotype were detected. Conclusion This study was the first investigation for an assessment of the prevalence of CCR5∆32 in northeastern Iran. The low prevalence of CCR5∆32 allele in the Iranian population may result in the increased susceptibility to HIV-1. In addition, this prevalence is the same as that of reported in East Asia, while is lower than that in the Europeans.